Disposição a pagar por alimentos orgânicos pelos consumidores de Fortaleza/Ce - Teles, Henrique Martins (2021)
Agribusiness in Brazil is one of the largest and most profitable economic activities in the country. According to the Systematic Survey of Agricultural Production, developed by IBGE, in December 2019, Brazil had about 78 million hectares of areas destined for food cultivation, where most of the cultivation is done through conventional agriculture. The use of this form of cultivation has been linked to environmental degradation and the threat to food security. In contrast to the conventional model of production, organic agriculture presents itself as an alternative form of agriculture. The practice of organic planting has several advantages, environmental and social, in comparison to the conventional one. Despite these advantages, this type of production is still little used compared to conventional production. Estimating the benefits of consuming organic food, through its willingness to pay, is relevant information for planning the expansion of the organic agricultural sector. However, valuation studies related to the consumption of organic foods are incipient in Brazil. Knowledge of consumer behavior contributes to support decision-making. Therefore, it is necessary to measure information about the real willingness of consumers to pay a higher amount (premium), for organic products compared to conventional products. That said, this study aimed to research whether consumers in Fortaleza are willing to pay a premium price to replace their food with conventional fruits and vegetables by organic ones. The Contingent Valuation Method (MVC) was used to measure this value. The results showed that families are willing to pay, positively, the amount of R $ 61.20 per month. It is noteworthy that the average DAP is influenced by the place where the respondent resides and the frequency of purchase of organic foods. Considering the number of families consuming conventional foods residing in the city of Fortaleza, the total benefit of replacing conventional with organic food generates a benefit of R $ 514,716,724,800. This value can serve as a reference for the economic feasibility analysis for projects to encourage organic production and stimulate investments in the organic market in the city of Fortaleza.